Pengaruh Profitabilitas, Modal, Dan Likuiditas Terhadap Discretionary Financing Loss Provisions Dengan Bank Size Sebagai Variabel Moderasi (Studi Pada Perbankan Syariah Di Indonesia 2016-2020) - Ihsan, Muhammad Fikri; Arif, Muhammad; Syahbudi, Muhammad (LP3kM Buddhi Dharma University, 2025)
This study analyzes the effect of profitability, capital, and liquidity on Discretionary Financing Loss Provisions (DFLP) with bank size as a moderating variable in Islamic banks in Indonesia from 2016 to 2020. Using a quantitative method and moderating regression analysis with SPSS, the results show that profitability, capital, and liquidity have a positive and significant effect on DFLP. Bank size does not moderate the effect of profitability on DFLP but can moderate the effect of capital and liquidity on DFLP. The F test indicates that all independent variables have a significant simultaneous effect on DFLP, as evidenced by the Fvalue (5.169) being greater than the Ftable value (2.54) and the significance value of 0.001 < 0.05. The coefficient of determination test shows that the R² value in model 1 is 0.273, and in model 2, it is 0.561. This indicates that the R² value in model 1 is smaller than in model 2, proving that adding moderation has a weak influence.